Assessing Implementation of the Principles for Public Credit Guarantees for SMEs : A Global Survey - Calice, Pietro (World Bank, Washington, DC, 2016)
This paper presents evidence on implementation of the World Bank Group and Financial Sector Reform and Strengthening Initiative "Principles for Public Credit Guarantee Schemes for Small and Medium Enterprises". The evidence is based on a self-assessment of 60 schemes in 54 countries. Overall, the results show a fairly decent level of implementation of the Principles, especially in the areas of legal and regulatory framework, mandate and eligibility rules, and claim management process. The results also show several gaps where reform and actions may be warranted, namely identification and accountability of funding sources, corporate governance and risk management, prudential regulatory recognition of guarantees, program/product calibration, and reporting and disclosure.